Circadian characterization of acumulation and utilization of non-structural carbohydrates in Erythrina velutina during late establishment - Silva, Maryelle Campos (2020)
We carried out a circadian characterization of the non-structural carbohydrate dynamics in the different organs of Erythrina velutina seedlings at late establishment. Seeds were incubated under controlled conditions for 9 days and then seedlings were hydroponically grown in a greenhouse for 8 days. Gas exchanges were measured in the cordiform leaves every 2 h during the daytime (12 h) and seedlings were harvested every 4 h during the day-night cycle (24 h) to assess the contents of non-structural carbohydrates and the activities of amylases and invertases. Photosynthetic net rate was highly synchronized with transpiration rate under high irradiance, when the cordiform leaves assumed the paraheliotropic position and water use efficiency increased. Diel patterns of non-structural carbohydrate content were identified in the photosynthetic organs, in which the turnover of starch operated far from its depletion at dawn. In the heterotrophic organs, however, changes in the starch content over 24 h may have maintained the supply of soluble sugars, buffering transient fluctuations in carbon availability. Although it seems that amylase activity was not influenced by the circadian rhythm in the different seedling organs, diel patterns of invertase activity were recognized in the leaves and roots.